Biowaste Sago Bark Based Catalyst Free Carbon Nanospheres: Waste to Wealth Approach - Gurumurthy, Hegde; Shoriya Aruni, Abdul Manaf; Anuj, Kumar; Gomaa, A M Ali; Kwok Feng, Chong; Zainab, Ngaini; K V, Sharma (American Chemical Society, 2015)
Catalyst free carbon nanospheres were synthesized using simple one step pyrolysis techniques where biowaste sago bark is used as a carbon precursor. Obtained carbon nanospheres showed porous nature and revealed that more than 95% carbon is present in the synthesized carbon nanospheres with particle size ranging from 40-70 nm. Electrochemical study showed specific capacitance value of 180 Fg-1 at 2 mVs-1 and the cycling stability up to 1700 cycles. Obtained carbon nanospheres are useful in super capacitor applications. Presented study revealed waste to wealth approach thereby reducing waste in the environment.